Optimizing the Definitions of Stroke, Transient Ischemic Attack, and Infarction for Research and Application in Clinical Practice - Abbott, Anne L.; Silvestrini, Mauro; Topakian, Raffi; Golledge, Jonathan; Brunser, Alejandro M.; de Borst, Gert J.; Harbaugh, Robert E.; Doubal, Fergus N.; Rundek, Tatjana; Thapar, Ankur; Davies, Alun H.; Kam, Anthony; et al. (Frontiers in Neurology, 2017)
Background and purpose: Until now stroke and transient ischaemic attack (TIA) have been clinically-based terms which describe the presence and duration of characteristic neurological deficits attributable to intrinsic disorders of particular arteries supplying the brain, retina or (sometimes) the spinal cord. Further, infarction has been pathologically defined as death of neural tissue due to reduced blood supply. Recently it has been proposed we shift to definitions of stroke and TIA determined by neuroimaging results alone and that neuroimaging findings be equated with infarction. Methods: We examined the scientific validity and clinical implications of these proposals using the existing published literature and our own experience in research and clinical practice. Results: We found that the proposals to change to imaging-dominant definitions, as published, are ambiguous and inconsistent. Therefore, they cannot provide the standardization required in research or its application in clinical practice. Further, we found that the proposals are scientifically incorrect because neuroimaging findings do not always correlate with the clinical status or the presence of infarction. In addition, we found that attempts to use the proposals are disrupting research, are otherwise clinically unhelpful and do not solve the problems they were proposed to solve. Conclusion: We advise that the proposals must not be accepted. In particular, we explain why the clinical focus of the definitions of stroke and TIA should be retained with continued sub-classification of these syndromes depending neuroimaging results (with or without other information) and that infarction should remain a pathological term. We outline ways the established clinically-based definitions of stroke and TIA, and use of them, may be improved to encourage better patient outcomes in the modern era.